Fundamentals of environmental site assessment and remediation - Rong, Yue, 1958- (Taylor and Francis, a CRC title, part of the Taylor and Francis imprint, a member of the Taylor and Francis Group, the academic division of T&F Informa, plc, 2018)
"This book will examine all aspects of environmental site assessment and remediation and outline the interdisciplinary skills needed to work in the field. It provides a comprehensive overview for students, environmental professionals, and real estate developers, and includes the latest environmental regulations, environmental site assessment and remediation practices, and industry standards. It examines pollution sources and the related impacts on drinking water supplies, the associated health risks, and how to protect water resources. The monitoring of surface water, groundwater, and soil is explained, as well as vapor intrusion. It will include several practical case studies throughout."--Provided by publisher.